Native albumin for targeted drug delivery - Neumann, Elena; Frei, Eva; Funk, Dorothee; Becker, Matthias D; Schrenk, Hans-Hermann; Müller-Ladner, Ulf; Fiehn, Christoph (Expert opinion on drug delivery, 2010)
Importance in the field: Activated cells metabolize albumin to cover their increased need for amino acids and energy. In inflamed, diseased and malignant tissue, extravasation of macromolecules into the tissue is upregulated. Drug carriers such as albumin have been used to target specifically diseased and malignant cells, resulting in higher efficacy of treatment and reduced side effects.Areas covered in this review: Owing to its advantageous biochemical and pharmacological properties, albumin has been regarded as an interesting candidate as a drug carrier. Covalent coupling to albumin carries drugs specifically to tumors and sites of inflammation, leading to reduced side effects as long as the native structure of albumin is unchanged. In this review, the means of coupling drugs to native albumin as well as exemplary studies for the use of albumin as drug carrier are summarized and discussed.What the reader will gain: An overview of the state-of-the-art using albumin as drug carrier for specific accumulation in tumors and inflammatory cells using the advantageous properties of native albumin is given in this review.Take home message: Native albumin is an effective drug carrier to sites of inflammation or malignancy.
Gesehen am 12.05.2023